1982
DOI: 10.1073/pnas.79.20.6255
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy of the dimeric iron site in azidomethemerythrin from Phascolopsis gouldii.

Abstract: X-ray absorption spectroscopy has been used to study the dimeric iron center in azidomethemerythrin from Phascolopsis gouldii Absorption edge data confirm that the two iron atoms are present as Fe(E) and suggest a hexa-coordination site for each of the iron atoms. The extended x-ray absorption fine structure (EXAFS) analysis provides direct structural evidence of a ,u-oxo bridge between the two iron atoms at an average Fe-O distance of 1. Hemerythrin has been studied by a variety of techniques (1-8) in attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…While the difference is not large, it is nominaly significant and can be justified on the basis of the different geometry of Fe(2) in the two complexes. The distances we observe can to be compared with the value of 3.34 (±0.07) Á reported by Hendrickson et al 21 for the Fe-Fe distance in the azidomet complex of myohemerythrin, based on the anomalous scattering differences in the X-ray diffraction data. Values of the Fe-Fe distance derived from EXAFS data are 3.4922 and 3.38 (±0.05) Á,21 these both being measurements of the Fe-Fe distances in azidomethemerythrin from P. gouldii.…”
Section: Discussion and Comparison Of Structuressupporting
confidence: 69%
“…While the difference is not large, it is nominaly significant and can be justified on the basis of the different geometry of Fe(2) in the two complexes. The distances we observe can to be compared with the value of 3.34 (±0.07) Á reported by Hendrickson et al 21 for the Fe-Fe distance in the azidomet complex of myohemerythrin, based on the anomalous scattering differences in the X-ray diffraction data. Values of the Fe-Fe distance derived from EXAFS data are 3.4922 and 3.38 (±0.05) Á,21 these both being measurements of the Fe-Fe distances in azidomethemerythrin from P. gouldii.…”
Section: Discussion and Comparison Of Structuressupporting
confidence: 69%
“…We had also learned from our experience in determining the structure of crambin from the weak anomalous scattering of Cu Kα x-rays by its intrinsic sulfur atoms that native anomalous scattering can suffice (Hendrickson & Teeter, 1981), and our experience in x-ray absorption spectroscopy of hemerythrin (Hendrickson et al, 1982) indicated that iron proteins might be excellent candidates. Thus, we successfully used lamprey hemoglobin as a first test subject (Hendrickson, 1985; Hendrickson et al, 1988).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The protein is typically an octamer with Mr = ~108 000 (Klippenstein, 1980;Klotz et al, 1976;Ward et al, 1975), and each monomer contains a nonheme iron binuclear center which reversibly binds one molecule of oxygen (Boeri & Ghiretti-Magaldi, 1957). The met form of Hr is known to have two high-spin Fe3+ ions with a large antiferromagnetic exchange coupling (Schugar et al, 1972) mediated by an endogenous µbridge, the presence of which was demonstrated by X-ray crystallographic (Stenkamp et al, 1985) and EXAFS studies (Hendrickson et al, 1982).Recently, the structures of the deoxy and oxy forms were solved at the level of 2.0-Á resolution, and the coordination environments around two irons were revealed in detail (Holmes et al, 1991); one iron (Fel) is always hexacoordinated, but the other (Fe2) is penta-or hexacoordinated depending on the two states. Fel and Fe2 are coordinated by three and two histidine residues, respectively, and are joined by the carboxyl side chains of glutamic and aspartic acid residues besides the µbridge.…”
mentioning
confidence: 99%
“…The protein is typically an octamer with Mr = ~108 000 (Klippenstein, 1980;Klotz et al, 1976;Ward et al, 1975), and each monomer contains a nonheme iron binuclear center which reversibly binds one molecule of oxygen (Boeri & Ghiretti-Magaldi, 1957). The met form of Hr is known to have two high-spin Fe3+ ions with a large antiferromagnetic exchange coupling (Schugar et al, 1972) mediated by an endogenous µbridge, the presence of which was demonstrated by X-ray crystallographic (Stenkamp et al, 1985) and EXAFS studies (Hendrickson et al, 1982).…”
mentioning
confidence: 99%